2019
DOI: 10.3390/medicina55110723
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral Cytotoxic T-Lymphocyte Density and PD-L1 Expression Are Prognostic Biomarkers for Patients with Colorectal Cancer

Abstract: Background and objectives: Cytotoxic T-lymphocyte (CTL)-mediated inflammatory response to tumors plays a crucial role in preventing the progression of some cancers. Programmed cell death ligand 1 (PD-L1), a cell-surface glycoprotein, has been reported to repress T-cell-mediated immune responses against tumors. However, the clinical significance of PD-L1 in colorectal cancer (CRC) remains unclear. Our aim was to elucidate the prognostic significance of PD-L1 expression and CD8+ CTL density in CRC. Materials and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 42 publications
3
25
0
Order By: Relevance
“…One such mechanism is the hijacking of intrinsic immune checkpoint mechanisms, notably the programmed death receptor‐1 (PD‐1) signaling pathway. PD‐ligand‐1 (PD‐L1) and, to a lesser extent, PD‐ligand‐2 (PD‐L2) can be expressed on tumor, immune, endothelial, and muscle cells 7‐10 . Binding of PD‐L1/PD‐L2 to PD‐1, expressed by activated lymphocytes, can attenuate adaptive anti–tumor immune responses 10 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…One such mechanism is the hijacking of intrinsic immune checkpoint mechanisms, notably the programmed death receptor‐1 (PD‐1) signaling pathway. PD‐ligand‐1 (PD‐L1) and, to a lesser extent, PD‐ligand‐2 (PD‐L2) can be expressed on tumor, immune, endothelial, and muscle cells 7‐10 . Binding of PD‐L1/PD‐L2 to PD‐1, expressed by activated lymphocytes, can attenuate adaptive anti–tumor immune responses 10 .…”
Section: Introductionmentioning
confidence: 99%
“…This may reflect the different underlying mechanisms of PD‐L1 expression by tumor cells and lymphocytes. Lymphocytes upregulate PD‐L1 expression in response to adaptive immune responses, so higher PD‐L1 expression may be reflective of higher levels of immune cell infiltration 7,9,10 . Whereas, in addition to cytokine‐induced expression, underlying genetic aberrations have been demonstrated to amplify the PD‐L1 gene in tumor cells, leading to constitutive expression of PD‐L1 and, therefore, an association with poor survival outcomes 9,19 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported that PD-L1 expression on tumor-infiltrating immune cells is correlated with the survival of patients with CRC ( 32 34 ). Moreover, the tumor microenvironment in CRC becomes infiltrated with T lymphocytes, which have the potential to activate the JAK/STAT signaling pathway following IFN-γ stimulation ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…The programmed cell death protein 1 receptor (PD-1), and its ligand programmed death ligand 1 (PD-L1), are one of most extensively studied immune checkpoints [2]. The PD-1 and PD-L1 are major co-inhibitory receptors that involved in T cell-mediated immunity [3]. The recognition between PD-L1 and PD-1 decreases T cell functions including the proliferation and Interleukin (IL)-2 cytokine release in the tumor microenvironment [4].…”
Section: Introductionmentioning
confidence: 99%